The Role of Responsiveness and Assurance in Enhancing Customer Satisfaction: Evidence from CIMB Niaga Bank, Mataram Branch - Baiq Solatiyah; Supiandi Supiandi (Program Studi Ekonomi Islam Fakultas Ekonomi Universitas Nahdlatul UlamaNusa Tenggara Barat, 2023)
This study examines the influence of service quality dimensions on customer satisfaction at CIMB Niaga Bank, Mataram Branch, Indonesia. The research aims to identify which aspects of service quality—tangibility, reliability, responsiveness, assurance, and empathy—most significantly affect customer satisfaction in the context of private banking services. Using a quantitative approach, data were collected through questionnaires distributed to 100 active customers and analyzed using multiple linear regression. The results reveal that responsiveness and assurance exert the strongest positive and significant effects on customer satisfaction, while tangibility, reliability, and empathy show weaker or statistically insignificant impacts. These findings suggest that customers value prompt service, competence, and trustworthiness more than physical appearance or empathy in determining their satisfaction with banking services. The study highlights that maintaining high responsiveness and assurance is crucial for sustaining customer loyalty and competitive advantage in the increasingly digitalized banking environment. Theoretically, the findings reinforce the SERVQUAL model by confirming the dominance of functional and relational service dimensions in shaping satisfaction in the Indonesian private banking context. Managerially, the study recommends continuous employee training in communication, problem-solving, and reliability to enhance the quality of customer experience.